On the rising complexity of bank regulatory capital requirements: From global guidelines to their United States (US) implementation - James R. Barth; Stephen Matteo Miller (Journal of Risk and Financial Management, 2018)
After the Latin American Debt Crisis of 1982, the official response worldwide turned to minimum capital standards to promote stable banking systems. Despite their existence, however, such standards have still not prevented periodic disruptions in the banking sectors of various countries. After the 2007-2009 crisis, bank capital requirements have, in some cases, increased and overall have become even more complex. This paper reviews (1) how Basel-style capital adequacy guidelines have evolved, becoming higher in some cases and overall more complex, (2) how the United States (US) implementation of these guidelines has contributed to regulatory complexity, even when omitting other bank capital regulations that are specific to the US, and (3) how the US regulatory measures still do not provide equally valuable information about whether a bank is adequately capitalized.
Keywords: G01; G28; K20; L51; N22; N42; 330; bank regulation; capital adequacy standards; regulatory complexity; US banking crises